Antiracist School Counselor Preparation: Expanding on the Five Tenets of the Transforming School Counseling Initiative - Erin Mason; Adrianne Robertson; Jan Gay; Nkenji Clarke; Cheryl Holcomb-McCoy (Teaching and Supervision in Counseling, 2021)
As a profession, school counseling must serve as an active force against systemic racism, and school counselor preparation must equip future professionals as antiracist agents of change. This article expands the original Transforming School Counseling Initiative (TSCI) tenets that sought to re-envision school counselor preparation in the late 1990s with language that explicitly supports antiracism. The authors offer a definition of antiracist school counseling and sample assignments and experiences that align with the revised tenets.
Keywords: School Counseling; Antiracism; Counselor Preparation